Inter-iconicity: discursive functioning of memory images - doi: 10.4025/actascilangcult.v35i4.20232 - Milanez, Nilton (2013)
The theoretic and methodological aspects which comprise the discursive functioning of images within a memory perspective are highlighted. Jean-Jacques Courtine, who first investigated the concept of discursive memory in French Discourse Analysis, was referring to inter-iconicity. The possibility deals with the historicity of images with regard to their formal traces as well as to the repetition of their discourses. The painting called As gêmas [The twins], 1940, by Brazilian painter Alberto Guignard, is focused to discuss the genealogical scheme of images which collaborate to the understanding and operationality of the concept under analysis.